2020
DOI: 10.1094/mpmi-07-19-0207-a
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Profiling of the Rice Blast Fungus Magnaporthe oryzae and Its Host Oryza sativa During Infection

Abstract: The rice blast (fungal pathogen: Magnaporthe oryzae and host: Oryza sativa) is one of the most important model pathosystems for understanding plant–microbe interactions. Although both genome sequences were published as the first cases of pathogen and host, only a few in planta transcriptome data during infection are available. Due to technical difficulties, previously reported fungal transcriptome data are not highly qualified to comprehensively profile the expression of fungal genes during infection. Here, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 20 publications
1
49
0
Order By: Relevance
“…Although the expression level of EFC genes increased during infection in both plants, the degree of induction in KJ201 appeared much higher than that in MoT isolate (Figure 7). However, additional experiments with more biological repeats and under identical environmental conditions are needed to validate this observation because the transcriptome data for KJ201 were obtained via rice sheath assay to enrich the quantity of fungal RNAs (Jeon et al, 2019), while the data from wheat plants were obtained samples collected in the field (Saunders et al, 2017). We also determined whether the presence of TEs in flanking regions of the EFC genes affect their expression, as some TEs have been suggested to affect the expression of EFC genes in other pathogens (Whisson et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the expression level of EFC genes increased during infection in both plants, the degree of induction in KJ201 appeared much higher than that in MoT isolate (Figure 7). However, additional experiments with more biological repeats and under identical environmental conditions are needed to validate this observation because the transcriptome data for KJ201 were obtained via rice sheath assay to enrich the quantity of fungal RNAs (Jeon et al, 2019), while the data from wheat plants were obtained samples collected in the field (Saunders et al, 2017). We also determined whether the presence of TEs in flanking regions of the EFC genes affect their expression, as some TEs have been suggested to affect the expression of EFC genes in other pathogens (Whisson et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…We analyzed transcriptome data from MoO isolate KJ201 (Jeon et al, 2019) and Bangladesh MoT isolate 12, a strain closely related to BR32 (Saunders et al, 2017). The data for KJ201 covered the mycelial stage in culture and the host infection stage at multiple time points [18, 27, 36, 45, and 72 h post-inoculation (hpi)].…”
Section: Methodsmentioning
confidence: 99%
“…We analyzed how the MoHTR genes are expressed during vegetative growth and in infected rice sheaths at the pre-penetration (18 hours post inoculation, hpi), biotrophic (27 and 36 hpi), transition (45 hpi), and necrotrophic (72 hpi) stages using available RNA-seq data 17 . Eleven genes were highly expressed during the biotrophic or transition stage, with their log 2 (FPKM+1) being ≥ 4.…”
Section: Resultsmentioning
confidence: 99%
“…We collected 1-kb upstream sequences from the coding region of all rice genes from the Rice Annotation Project Database (RAP-DB) 38 and checked the presence of each EBE. Differentially expressed genes (DEGs) at 36 hpi (biotrophic stage) were identified using transcriptome data generated from infected rice sheaths 17 . Gene ontology (GO) enrichment analysis was performed using RiceNetDB 25 .…”
Section: Methodsmentioning
confidence: 99%
“…Rice blast, caused by M. oryzae, is the most devastating disease of rice and threatens food security worldwide. In M. oryzae-rice interaction, the majority of the effectors are kept transcriptional silencing or expressed relatively low in the vegetative growth stage (Dong et al, 2015, Sharpee et al, 2017, Jeon et al, 2020, but are derepressed during invasive growth stage (Dong et al, 2015, Jeon et al, 2020. During preparing our manuscript, a really good study found that H3K27 dynamics associate with altered transcription of in planta induced genes in M. oryzae (Zhang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%